(untitled) (Forum for Linguistic Studies, 2024)
In the pursuit of holistic health and well-being, the convergence of ancient contemplative practices and contemporary mental health interventions, particularly yoga and meditation, has gained considerable attention. This study, titled "From Mat to Mind," explores the transformative impact of yoga and meditation on emotional well-being. Examining the literature, we find substantial evidence supporting the positive effects of these practices on emotional resilience, anxiety, depression, and neurobiological mechanisms However, a comprehensive understanding of their specific impact necessitates rigorous research. This study also explores the impact of integrating yoga and meditation practices within the framework of Indigenous Knowledge Systems (IKS) on sustainable emotional well-being. Recognizing the holistic nature of IKS, which emphasizes the interconnectedness of mind, body, and spirit, we investigate how incorporating yoga and meditation into healthcare initiatives aligns with and enhances traditional approaches to well- being. This research employs a mixed-methods design, combining a randomized controlled trial with real-time internet data analysis, to assess the emotional well-being of participants engaged in yoga and meditation interventions. The study includes a diverse sample aged 18-60, employing self- report measures, physiological data, and real-time internet data to evaluate outcomes. Preliminary results reveal positive changes in emotional well-being, increased online engagement, and physiological improvements in both intervention groups, emphasizing the potential of digital platforms in enhancing accessibility to mind-body interventions. The study contributes valuable insights to the field, highlighting the promise of integrating traditional and digital approaches for widespread mental well-being promotion.